Evaluations of bacterial contaminated full thickness burn wound healing in Sprague Dawley rats Treated with Tualang honey - Salmi Mohamed Sukur; Ahmad Sukari Halim; Kirnpal Kaur Banga Singh (Indian Journal of Plastic Surgery)
Aim: The effect of Tualang honey on wound healing in bacterial contaminated full-thickness burn wounds was evaluated in 36 male Sprague Dawley rats. Materials and Methods: The rats were randomly divided into three groups (n = 12/group). Three full-thickness burn wounds were created on each rat. Each group of rats was inoculated with a different organism in the burn wounds: Group A was inoculated with Pseudomonas aeruginosa, Group B was inoculated with Klebsiella pneumoniae and Group C was inoculated with Acinetobacter baumannii. One wound on each rat was dressed with either Tualang honey, Chitosan gel or Hydrofibre silver. Each wound size was measured on day 3, 6, 9, 12, 15, 18 and 21 of the study. Results: The mean wound size of the Tualang honey-treated wounds was not statistically different than that of the Chitosan gel or Hydrofibre silver-treated wounds when the wounds were compared throughout the entire experiment (P > 0.05). However, comparing the mean wound size on day 21 alone revealed that the Tualang honey-treated wounds were smaller in comparison to that of the Chitosan gel and Hydrofibre silver-treated groups. Conclusions: This study shows that topical application of Tualang honey on burn wounds contaminated with P. aeruginosa and A. baumannii gave the fastest rate of healing compared with other treatments.